‘Marching to Someone Else’s Beat or Creating Your Own Groove?’ Towards a Rhythmic Understanding of Context, (Entrepreneurial) Agency, and Transformative Change - Dey, Pascal; Teasdale, Simon (Journal of Management Studies, 2026)
Abstract How contexts shape organizational phenomena has long been a focus of management and organization studies (MOS), as has how actors influence contexts. This paper deepens this debate using a rhythm perspective, developed against the backdrop of entrepreneurship research, which has made context a priority but not fully clarified how entrepreneurial agency alters contextual conditions. Drawing on Henri Lefebvre’s Rhythmanalysis , we argue that the everyday provides a privileged vantage point for understanding how contextual forces permeate entrepreneurship and, conversely, how they are affected by it. Specifically, we theorize that the everyday forms a diverse and shifting symphony of rhythms, and suggest that entrepreneurial agency includes the transformative capacity to shape these rhythms to create tangible value. We refine our theorizing through the example of the Brukman textile factory, an entrepreneurial squat taken over by its former workers. The vignette explores how agency is enacted through the cultivation of moments of rupture ( arrhythmia ) and moments of rhythmic harmony ( eurhythmia ). Our contribution is to develop a rhythm perspective to spark new ways of thinking about context, agency, and transformative change. While our theorizing is rooted in entrepreneurship research, we identify ways in which it can stimulate MOS more broadly.